Trigger Factors of Fraud Triangle Toward Fraud On Financial Reporting Moderated by Integration Of Technology Industry 4.0 - Mappadang, Agoestina; Yuliansyah, Yuliansyah (Jurnal Ilmiah Akuntansi dan Bisnis, 2021)
This study examines triggers factors of the fraud triangle, core of all fraud auditing standards, for assessing the likelihood of fraudulent financial reporting. The Fourth Industrial Revolution (Industry 4.0) brings vital changes to industries, which forces people to face and act on these changes and may get impacted on fraudulent financial reporting. As Industry 4.0 ushers the use of new technology, the use of computerized systems for huge data analysis has advantage and disadvantage in audit and fraud detection. Therefore, our research uses the integration of technology 4.0 as a moderating variable on fraudulent financial reporting. This study also aims to determine fraud with the Beneish M-Score as a financial forensic tool to gage potential fraud in firms' financial statements. The population of this study was drawn from five priority sectors of the Making Indonesia 4.0 program, namely industries in five manufacturing subsectors listed on the Indonesia Stock Exchange. Results indicate that pressure does not have significant effect on fraudulent financial reporting. On the other hand, the opportunity with effective monitoring variable has a negative significant effect on fraudulent financial reporting, whereas rationalization has a positive significant effect on fraudulent financial reporting. The integration of Industry 4.0 variable moderates the effect of fraud on fraudulent financial reporting. Keywords:  fraud triangle, technology industry, pressure, opportunity, rationalization